Penguatan Peran Ibu Sebagai Terapis Anak Usia Dini - Kiftiyah Kiftiyah; Denok Wigati; Inayatul aini; Dhita Kristianingrum; Imam Fatoni; Siti Shofiyah Shofiyah (Jurnal Pengabdian Masyarakat Universitas Darul Ulum, 2025)
Abstract. This community service program aims to strengthen the role of mothers as emotional therapists for early childhood through psychoeducation and emotional support practices. The activity was held at the Cukir Sugar Factory Kindergarten, Jombang Regency, on December 17, 2025, targeting 34 participating mothers. The method used was practice-based psychoeducation, which included the delivery of material on early childhood emotional development, interactive discussions, simulations, role plays, and direct practice in using emotional therapy sentences when accompanying children. The activity was evaluated through pre- and post-measurements of the mothers' understanding, observations during practice, and joint reflection with the participants. The results of the activity showed an increase in mothers' understanding of the functions and types of children's emotions, an increase in their ability to respond to children's emotions empathetically, and an increase in their skills in using emotional therapy sentences. In addition, mothers' confidence in accompanying their children's emotions also increased after participating in the activity. The impact of the community service was seen in the change in the pattern of interaction between mothers and children, which became warmer, more responsive, and more supportive of children's emotional regulation. This activity also strengthened the synergy between the school and parents in supporting the social-emotional development of early childhood. This community service program is expected to become a model for simple, applicable psychoeducational interventions that can be replicated in other early childhood education units.